The coupling effect of ventilation and groundwater flow on the thermal performance of tunnel lining GHEs. (5th February 2017) - Zhang, Guozhu; Liu, Songyu; Zhao, Xu; Ye, Meixi; Chen, Runfa; Zhang, Hualin; Yang, Junda; Chen, Jiawei
Highlights: Thermal response model tests under ventilation and groundwater were carried out. Thermal performance under ventilation and groundwater was evaluated. Ventilation and groundwater enhance the heat exchange rate of tunnel lining GHEs. Abstract: Tunnel lining ground heat exchangers (GHEs) in this paper have advantages such as not requiring extra space, a low construction cost, and more efficient in heat exchange, offering a solution to the utilization of geothermal energy in central urban areas. Ventilation and groundwater flow are two important factors that significantly affect the underground temperature field. Laboratory model tests were carried out to evaluate the coupling effect of ventilation and groundwater flow on the thermal performance of tunnel lining GHEs. The test results show that (i) ventilation enhances the heat exchange process between the GHEs and the surrounding rock; (ii) the depth to which the GHEs influence the surrounding rock temperature field in the downstream of the groundwater flow field is 2.6 times higher than that in the upstream, and the ventilation and groundwater flow aggravate uneven distribution of the temperature field of the surrounding rock, so the heat exchange pipes should be installed in the upstream of the groundwater flow field; (iii) the coupling heat transfer between air and lining should be taken into consideration when the heat exchange rate of the heat exchange pipe is calculated.